A Comparative Study of IT Integration in TU Programs: BICTE, BIM, and BCA in Nepal - Khatiwada, Shreeraj (International Research Journal of MMC, 2025)
This study presents a comparative analysis of three IT-integrated undergraduate programs offered by Tribhuvan University in Nepal: BICTE, BIM, and BCA. Each program serves different academic goals, BICTE prepares ICT educators, BIM blends IT with business, and BCA focuses on core computing. The research aims to help students make informed academic choices by analyzing the IT curriculum, practical components, and career relevance of each program. A mixed-methods approach was used, involving curriculum document review and surveys with students, lecturers, and alumni. Although each program is designed with a distinct purpose, the results indicate that for building a career in diverse IT fields, BCA provides the strongest technical foundation with extensive hands-on training, BIM offers a balanced approach suitable for IT-business careers, and BICTE, while focused on theory and education, requires improved practical exposure to broaden its career relevance. Stakeholders highlighted the need for updated content and real-world skill development, especially in BICTE. The findings support curriculum improvements and offer clear guidance for prospective students and educators.